Sintering effect on the microstructural, mechanical, and in vitro bioactivity properties of a commercially synthetic hydroxyapatite - SALMAN, SERDAR; PAZARLIOĞLU, SÜLEYMAN SERDAR (SPRINGER, 2017)
This study is related to the effect of sintering on a commercially synthetic hydroxyapatite powder (CSHAp) uniaxially pelleted and sintered at various temperatures. A series of thermal analysis methods and tests were used to evaluate both phase changes that occurred during sintering and physical and mechanical properties of sintered samples. Bioactivity property of CSHA was investigated in SBF solution during 3, 7, 15, and 30 days. The results show that changes in colors occur in sintered samples at 1200 and 1300 degrees C. Phase changes occur in HA beta-TCP at 1200 degrees C and HA beta TCP, alpha-TCP, and CaO phases at 1300 degrees C at less than 5% of each phases. The hardness and density values attain to maximum value of 4.87 +/- 0.15 GPa and 3.06 +/- 0.02 g/cm(3) with 98.35 +/- 0.17% relative density at 1300 degrees C, respectively. However, its compressive and flexural strengths increase by increasing sintering temperature until 1100 degrees C (130.20 +/- 6.22 MPa for scompressive and 60.27 +/- 9.93 MPa for sflexural) and then drastically decrease at elevated temperatures. Its fracture toughness and average grain size values change between 0.68 +/- 0.05 and 0.96 +/- 0.05 MPam(1/2) and 0.162 +/- 0.019 and 17.167 +/- 2.156 mu m. Apatite crystals occur on the surface of CSHAp as needle at 3 days and they grow by ascending dwelling time.
Keywords: Commercially synthetic hydroxyapatite; Sintering; X-ray diffraction; Scanning electron microscopy; Physical andmechanical properties; Simulated body fluid; GLASS-REINFORCED HYDROXYAPATITE; CALCIUM-PHOSPHATE CERAMICS; BIOCERAMICS; PARTICLES; STRENGTH; POROSITY; SCAFFOLD